Evaluation of Redundancy Methods and Strategies for the On-Board Spectral Reference of the NOAA CrIS Instruments - Beierle, Peter J.; Iturbide-Sanchez, Flavio; Tremblay, Denis; Predina, Joseph P.; Zhang, Kun; Chen, Yong; Johnson, David G.; Glass, Sara; Strow, L. Larrabee (IEEE, 2026)
The cross-track infrared sounder (CrIS) is an infrared Fourier transform spectrometer (FTS) hosted on the Joint Polar Satellite System (JPSS). To produce a CrIS sensor data record (SDR) with high-quality spectral calibration, it is necessary to accurately and periodically calibrate CrIS interferometer metrology laser wavelength over time (i.e., a spectral calibration reference). The current spectral calibration reference method makes use of a neon lamp’s highly stable gas emission spectral line processed through the FTS. Further improvements in spectral calibration reliability have been developed using alternative methods described in this article which provide redundancy to the in-orbit neon lamp spectral calibration reference. The first proposed redundancy method involves a real-time regression algorithm which uses the known correlation between the laser diode’s output wavelength and the laser diode temperature to provide updated estimates of the metrology laser wavelength. A second proposed method uses simulated atmospheric line absorption and emission radiances as a spectral reference to estimate the spectral changes in the FTS laser metrology wavelength. Starting with NOAA-21 CrIS and for all other future CrIS sensors, the periodicity of calibrating the laser’s wavelength was changed from approximately once per satellite orbit to once every seven orbits to extend the neon lamp’s useful lifetime. Here we present the estimated impact of changing the interval between neon lamp measurements of the CrIS metrology laser wavelength, along with studies of these two redundancy methods and their assessment in an operational environment.
Keywords: Fourier transform spectrometer (FTS); Community radiative transfer model (CRTM); UMBC Atmospheric Spectroscopy Lab; Redundancy; cross-track infrared sounder (CrIS); Joint Polar Satellite System (JPSS); Distributed feedback devices; Diode lasers; Measurement by laser beam; Temperature measurement; spectral calibration; Earth; interferometer; Calibration; metrology laser wavelength; Neon; Metrology; Semiconductor lasers; neon lamp